2023
DOI: 10.3390/ijms24044206
|View full text |Cite
|
Sign up to set email alerts
|

A Dual-Modality Imaging Method Based on Polarimetry and Second Harmonic Generation for Characterization and Evaluation of Skin Tissue Structures

Abstract: The characterization and evaluation of skin tissue structures are crucial for dermatological applications. Recently, Mueller matrix polarimetry and second harmonic generation microscopy have been widely used in skin tissue imaging due to their unique advantages. However, the features of layered skin tissue structures are too complicated to use a single imaging modality for achieving a comprehensive evaluation. In this study, we propose a dual-modality imaging method combining Mueller matrix polarimetry and sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 74 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…For SHG imaging, a dichroic mirror, a custom filter set (BP:414/46, DC:495, BP:525/50), and a 20×water immersion objective are employed. Figure 2(e) displays the SHG image of the tissue sample [13].…”
Section: Mueller Matrix Microscope and Mueller Matrix Polar Decomposi...mentioning
confidence: 99%
See 1 more Smart Citation
“…For SHG imaging, a dichroic mirror, a custom filter set (BP:414/46, DC:495, BP:525/50), and a 20×water immersion objective are employed. Figure 2(e) displays the SHG image of the tissue sample [13].…”
Section: Mueller Matrix Microscope and Mueller Matrix Polar Decomposi...mentioning
confidence: 99%
“…Mueller matrix polarimetry is characterized by high information content, not requiring staining or labeling, and being sensitive to subcellular microstructures [7][8][9][10][11][12][13]. It can also provide additional sample structural information by integrating with existing optical systems such as microscopes [14].…”
Section: Introductionmentioning
confidence: 99%
“…12 For microscopic polarization imaging of thin tissue slices, linear birefringence is a valuable and prevalently used metric for anisotropic structures characterization. [13][14][15] For instance, Wood et al 16 demonstrated that linear birefringence can be adopted for in vivo tissue fiber characterization. Furthermore, Pierangelo et al 17 showed that the reducing of linear birefringence resulting from the breaking down of well-ordered fibrous structures can be used for cervical cancer identification.…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of a single-shot Mueller polarimeter can reduce the number of measurements, the system becomes very costly [34][35][36]. In the present manuscript, we introduce a novel approach: multispectral Stokes imaging, which only requires six intensity measurements.…”
Section: Introductionmentioning
confidence: 99%
“…However, traditional Mueller matrix imaging requires a large number of intensity measurements, specifically 24 measurements, which are time‐consuming and require complex optical setups and their alignment. Although the use of a single‐shot Mueller polarimeter can reduce the number of measurements, the system becomes very costly [34–36]. In the present manuscript, we introduce a novel approach: multispectral Stokes imaging, which only requires six intensity measurements.…”
Section: Introductionmentioning
confidence: 99%